Relationship of Population Growth and Cereal Grains Availability in Burundi: ARDL Model Estimation - Egide, Bizimana; Leonard, Ntakirutimana; Nicodeme, Nimenya; Abel, Bigawa Bazira (Current Approaches in Engineering Research and Technology Vol. 5, 2024)
Food scarcity is an important problem for the growing population of the globe. The study aims to discuss the relationship between population growth and the availability of cereal grains in Burundi. Food availability and population growth have long been of concern to researchers. The data was obtained from the sites of the FAO, World Bank and Climate Change Knowledge Portal (CCP). The ARDL model and bounds co-integration test were used in STATA 14.2 for estimating the growth population effect on the availability of rice and maize in the short and long run in Burundi. The findings showed that ECT is negatively significant for both items at 1% level and therefore the long-run equilibrium can be reached. Annually, the coefficient of ECT for maize production is equal to -0,394 meanwhile this for rice production is equal to -0,813. Population growth (PGR) is a major factor in food availability because when this variable increases by one unit, in the short term, rice production increases by 0.524%. However, the increase of one percent of the rural population (RPR) in the first instance implies a decrease of 0.407% of rice in the short term. However, in the long term, increasing this variable by one percent implies a reduction in the production of 0.122% for maize and 1.337% for rice annually. In the long run, the contribution of the population growth (PGR) is not significant for the two items and the sign is different from one to another. The government should therefore put in place a new land use planning policy by creating villages in order to remedy the problem of land fragmentation, a birth control policy, and a price stabilization policy in order to end the food deficit.